2013
DOI: 10.1179/2042618613y.0000000048
|View full text |Cite
|
Sign up to set email alerts
|

A survey of physical therapists’ clinical practice patterns and adherence to clinical guidelines in the management of patients with whiplash associated disorders (WAD)

Abstract: Advanced certification and knowledge of guidelines appeared to play a role in the clinical practice of physical therapists treating patients with WAD. Further research is needed to explore factors affecting knowledge translation from research to clinical practice and to evaluate the outcomes of patients with WAD when clinical guidelines are applied in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…Some of them might have used outcome measures in their research projects which might have resulted in more familiarity with SOMs. This is similar to a study that showed that advanced certification and knowledge of guidelines appeared to play a role in the clinical practice of physiotherapists treating patients with whiplash-associated disorders (Corkery, Edgar & Smith 2014 ).…”
Section: Discussionsupporting
confidence: 86%
“…Some of them might have used outcome measures in their research projects which might have resulted in more familiarity with SOMs. This is similar to a study that showed that advanced certification and knowledge of guidelines appeared to play a role in the clinical practice of physiotherapists treating patients with whiplash-associated disorders (Corkery, Edgar & Smith 2014 ).…”
Section: Discussionsupporting
confidence: 86%
“…After removing duplicates and screening 8567 titles and abstracts and 254 full-texts reports, 94 studies were included (figure 1). Physical therapy treatment choices were investigated for low back pain (n=48 studies),11–58 knee pain (n=10),32 34 57 59–65 neck pain or whiplash (n=11),15 18 32 34 51 66–71 foot or ankle pain (n=5),72–76 shoulder pain (n=7),15 51 77–81 pre or post knee arthroplasty (n=6)46 82–86 (including one study of hip and knee arthroplasty86) and other musculoskeletal or orthopaedic conditions (where treatment choices were only reported in one study or where one of either recommended or not recommended treatments could not be inferred from guidelines or systematic reviews) (n=18) 87–104. We contacted 15 authors for data (regarding 18 studies): 12 responded and 5 were able to provide the data we requested (regarding six studies) 15 16 22 64 89 100.…”
Section: Resultsmentioning
confidence: 99%
“…Disagreement with blanket recommendations and valuing clinical experience over evidence could explain why some physiotherapists do not use guidelines to inform their treatment choices 10 13 18 19. For example, previous research found only 46% of physiotherapists believe guidelines should inform the management of low back pain (survey of n=274),11 66% apply guidelines to more than half of their patients with acute ankle sprains (survey of n=214)18 and 39% use guidelines to inform the management of whiplash more than three-quarters of the time (survey of n=237) 19. Challenging these beliefs could be an important first step towards replacing low-value care with evidence-based care in physiotherapy.…”
Section: Discussionmentioning
confidence: 99%